Determination of Suitable Areas for Physical Development of Cities Based on Geomorphological Parameters (Case Study: Baneh City) - Morteza Akbarian; Dyana Dortaj (جغرافیا و پایداری محیط)
The trend of urban development has led to the emergence of areas facing residential areas in recent years. Meanwhile, cities in the mountainous areas are more likely to face this problem. Baneh is one of the cities of mountainous areas in the west of the country, which has a rapid development of urban development. Considering the importance of the issue, in this research, the areas that are prone to developing settlements in the city of Baneh have been investigated. In this research, in order to achieve the desired goals, eight lithology parameters, distance from fault, elevation, slope, direction, distance from the river, land use, and communication distance have been used. After providing information layers and fuzzing them, they are weighted by using the AHP model, and the resulting weight is then applied to the information layers and eventually the information layers are combined with the use of the fuzzy gamma operator; the final map is obtained. The resulting map combines information layers into five classes, which are very large, medium, low, and very much proportionate. The assessment of classes indicates that only about 30% of the study area is in very high proportion, indicating that Baneh City has many limitations for the purposes of urban development.